2019
DOI: 10.1080/13573322.2019.1676221
|View full text |Cite
|
Sign up to set email alerts
|

The continued importance of family sport culture for sport participation during the teenage years

Abstract: Growing up in a family with an affinity for sports increases the likelihood of participating in club-organised sports. Few studies to date have addressed whether the importance of family sport culture is stable or changes during the teenage years. This article examines the association between family sport culture and participation in club-organised sports during teenage years and whether it differs between boys and girls. We utilise data from Norway and the comprehensive 'Young in Oslo 2015' survey (N = 6121; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 42 publications
6
49
0
6
Order By: Relevance
“…Family sport culture has a consistent and enduring effect on young people participating in sports. 26 In spite of the coaches’ proximal environment, Berntsen and Kristiansen 27 found that controlling behavior by coaches can decrease motivation in athletes. Thus, the influence of teammates’ support on student-athletes requires empirical evidence to link the relationship between social support and positive emotions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Family sport culture has a consistent and enduring effect on young people participating in sports. 26 In spite of the coaches’ proximal environment, Berntsen and Kristiansen 27 found that controlling behavior by coaches can decrease motivation in athletes. Thus, the influence of teammates’ support on student-athletes requires empirical evidence to link the relationship between social support and positive emotions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Respondents' own sports background will likely influence which sports they prefer children to play and how strongly they might encourage each sport (Strandbu, Bakken, and Stefansen 2019).…”
Section: Sports Background and Sociodemographic Factorsmentioning
confidence: 99%
“…In this study, we examine how American adults' attitudes about youth sport participation are associated with their political beliefs including sports related patriotic sentiment, and social position, including race, educational attainment, income, and attention to concussion related news. In an era of political polarization, Americans are divided along partisan lines in terms of all manner of preferences and patterns of social behavior (Mason 2018;Bishop and Cushing 2008;Sussell 2013;Shi et al 2017;Friedland et al 2007), leading many to describe it as a "culture war" (Alwin and Tufiş 2015;Fiorina et al, 2005). Though our cultural preferences are important ways of signaling group membership and fundamental socio-political values, they can also have potentially significant consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Almost six out of ten who have participated in youth sports have quit before they turn eighteen years old [ 14 ]. There is a precipitous decline in physical activity and participation in organized sports across the teenage years, highlighting the need to understand influences on PA and sports participation among young people [ 14 – 16 ]. Adolescence is a critical time to develop PA patterns which extend to adulthood [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%